Impact of the COVID-19 Pandemic on Microbial Profiles and Clinical Outcomes in Orbital and Preseptal Cellulitis - Yu-Ting Tsao; Yueh-Ju Tsai; Chau-Yin Chen; Yen-Chang Chu; Yun-Shan Tsai; Yi-Lin Liao (Microorganisms, 2024)
Orbital cellulitis and severe preseptal cellulitis are critical periocular infections with potential vision- and life-threatening implications. The COVID-19 pandemic is hypothesized to have had an influence on their presentation and pathogenesis; however, the real impact remains unclear. In this retrospective multicenter cohort study from January 2017 to December 2022, we analyzed 1285 cases with preseptal or orbital cellulitis in pre-pandemic (2017–2019) and pandemic (2020–2022) cohorts. A notable decrease in hospitalized cases during the pandemic period was observed (97 patients in the pre-pandemic group vs. 54 in the pandemic group, p = 0.004), particularly among individuals aged 30–39 (p = 0.028). Sinusitis remained the leading cause, but odontogenic cases increased (p = 0.025). In addition, microbial diversity decreased during the pandemic, with the effective number of species decreasing from 17.07 to 8.87, accompanied by a rise in antibiotic resistance, notably against erythromycin, oxacillin, penicillin, and metronidazole. While visual outcomes appeared worse in the pandemic group, statistical significance was not reached. These findings suggest that the characteristics, etiology, microbial profiles, resistance patterns, and visual outcomes of orbital and preseptal cellulitis have undergone alterations post-COVID-19 pandemic. Vigilance in clinical management and public health measures is crucial, with further research needed to optimize treatment strategies.